TECHNICAL EFFICIENCY ANALYSIS OF RAINFED WETLAND RICE FARMING IN SUMBER SARI VILLAGE, BABULU SUB-DISTRICT, PENAJAM PASER UTARA DISTRICT - Arjuna, Rezahani Dimas; Hanani, Nuhfil; Toiba, Hery (Agricultural Socio-Economics Journal, 2024)
Rice is a staple food in Indonesia which has an impact on the high demand for it. One thing that can be done to increase the productivity of rice farming is to utilize existing resources as efficiently as possible (technical efficiency). This study aims to analyze the technical efficiency of wet-rice farming and to analyze the factors that influence the technical efficiency of farming in Sumber Sari Village, Babulu Subdistrict, Penajam Paser Utara Regency. This research was conducted by direct observation to the research location and interviews with respondents, which were 53 farmers who had met the inclusion criteria. The results were then analyzed using the Data Envelopment Analysis (DEA) approach. Based on the research that has been done, it can be seen that the calculation of technical efficiency with constant to scale (CRS) has an average technical efficiency value of 0.954. While for the calculation of technical efficiency with variable return to scale (VRS), the average value of efficiency is 0.999. Factors that affect the production of rice farming include land area (X1), seed (X2), fertilizer (X3) and pesticides (X4). Meanwhile, labor (X5) which is a factor that does not affect the production of rice farming in this study.